2020
DOI: 10.1093/gigascience/giaa036
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome-level reference genome of the jellyfish Rhopilema esculentum

Abstract: Background Jellyfish belong to the phylum Cnidaria, which occupies an important phylogenetic location in the early-branching Metazoa lineages. The jellyfish Rhopilema esculentum is an important fishery resource in China. However, the genome resource of R. esculentum has not been reported to date. Findings In this study, we constructed a chromosome-level genome assembly of R. esculentum using Pacific Biosciences, Illumina, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 61 publications
3
39
0
Order By: Relevance
“…This stands in stark contrast to the genome of the jelly sh Rhopilema esculentum. In Rhopilema, recent Hi-C analysis suggested the existence of 21 chromosomes, in line with the earlier analyses of chromosome spreads 11,36 . We observed that all Rhopilema and Nematostella chromosomes show a clear 1-to-1, 1-to-2 or, in a single case, a 1-to-3 correspondence (Figure 5a).…”
Section: Supplementary Text)supporting
confidence: 77%
“…This stands in stark contrast to the genome of the jelly sh Rhopilema esculentum. In Rhopilema, recent Hi-C analysis suggested the existence of 21 chromosomes, in line with the earlier analyses of chromosome spreads 11,36 . We observed that all Rhopilema and Nematostella chromosomes show a clear 1-to-1, 1-to-2 or, in a single case, a 1-to-3 correspondence (Figure 5a).…”
Section: Supplementary Text)supporting
confidence: 77%
“…Nevertheless, the function of EGF_CA domains has not been well understood in aquaculture animals. With the release of genomic information of R. esculentum 14 and the development of biotechnology, the gene function studies of R. esculentum will be improved and more genes will be investigated for genetic breeding.…”
Section: Discussionmentioning
confidence: 99%
“…The genes located on the up-and down-stream 500 Kb distance of the associated genomic region of body weight and umbrella diameter were detected 14,50…”
Section: Genome-wide Association Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the toxins in this family share sequence similarity with ryncolins, a group of hemostasis-impairing toxins originally described from C. rynchops [ 21 ]. Ryncolin genes [ 22 ], transcripts, and proteins [ 23 , 24 , 25 , 26 ] have also been found in other species of jellyfish, but their functions are not well-characterized. C-type lectins, another major group of hemostasis-impairing toxins, are commonly found in the venoms of a wide variety of animals [ 27 , 28 , 29 , 30 ], including several jellyfish species: Pacific sea nettle Chrysaora fuscescens [ 31 ], Lion’s mane jellyfish Cyanea capillata, Nomura’s jellyfish N. nomurai [ 26 ], and cannonball jellyfish Stomolophus meleagris [ 23 ].…”
Section: Discussionmentioning
confidence: 99%